Collaborative Governance and Smart Public Services for Sustainable Development in West Papua Province - Salmawati Salmawati; Fauziah Saragih; Masni Banggu; Mohammad Saleh Refra; Muhammad Zuhdan; Alfatihah Devi Auliya (Jurnal Noken: Ilmu-Ilmu Sosial, 2026)
The establishment of Southwest Papua Province under Law No. 29 of 2022 has created significant challenges for sustainable development, including limited institutional capacity, unequal public service accessibility, and inadequate digital infrastructure. Although collaborative governance and smart public services have received increasing scholarly attention, their integrated role in supporting sustainable development in newly autonomous regions remains underexplored. This study examines the influence of collaborative governance and smart public services on sustainable development outcomes in Southwest Papua. An explanatory sequential mixed-methods design was employed. Quantitative data were collected through a questionnaire survey of 412 respondents and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The quantitative findings were subsequently validated and enriched through semi-structured interviews with 22 key stakeholders. The results indicate that collaborative governance has a significant positive effect on both smart public services and sustainable development outcomes. Smart public services further enhance sustainable development by improving service accessibility, efficiency, and transparency. Qualitative findings emphasize stakeholder participation, inter-organizational coordination, Indigenous community engagement, and digital innovation as critical drivers of governance effectiveness, while limited digital infrastructure and uneven internet access remain major constraints.